El papel de las competencias laborales en el ámbito educativo: una perspectiva de reflexión e importancia. - Castillo Sarabia, José Crescencio; Villalpando Cadena, Paula (Revista Daena: International Journal of Good Conscience, 2019)
The present research work tries to show the different national and international efforts, to conceptualize the term of competences, in its approach to education and its subsequent transit and implementation in the workplace, with the priority of contributing to raise the indexes of productivity and competitiveness in companies and their respective countries. Even though there are important initiatives and decision-making at governmental and institutional levels, to promote reforms in education systems and to guide the training of individuals towards the development of competencies, the scope of this work allows us to visualize what could be considered as the main barrier or lag in the effective implementation of educational programs and their application in the operation of companies. Considering that the most accessible concept of labor competencies, would be precisely the approach to each of the contexts in which it is intended to be used.